How do macroprudential policies affect corporate investment? Insights from EIBIS data - Koray Alper; Soner Baskaya; Shuren Shi (European Investment Bank (EIB), 2025)
This study investigates the influence of macroprudential policies (MaPs) on corporate investment, employing firm-bank level microdata from the European Investment Bank Investment Survey (EIBIS) for the period 2015-2022. We initially document that MaP tightening, particularly through supply-based MaPs, leads to a reduction in corporate investment. We then delve into the transmission mechanism of MaPs. Our analysis suggests that MaPs affect corporate investment through bank lending decisions. MaP tightening correlates with greater reliance on internal finance and reduced use of external finance. Further, we find that both bank and firm characteristics significantly contribute to the effect of MaPs on corporate investment. Specifically, we observe that financially weaker banks are more likely to restrict credit in response to MaP tightening. Moreover, firms that are heavily reliant on external finance for investment, as well as those that are financially weaker, appear to be more adversely affected by a reduced credit supply. Lastly, we find that MaPs exert a stronger impact on tangible investments, whereas intangible investments are less sensitive to MaPs. Our finding suggests that the insignificance is due to the lower reliance of intangible investments on external finance, verifying the presence of the bank lending channel of MaP transmission.
Keywords: D22; E22; E58; G28; 330; Macroprudential policies; bank lending; tangible investments; intangible investments; financial stability